Biparental defensive endowment of eggs with acquired plant alkaloid in the moth Utetheisa ornatrix. - Dussourd, D E (1988)
The eggs of Utetheisa ornatrix contain pyrrolizidine alkaloids. These compounds are contributed by both parents, who sequester them as larvae from their food plants. Females receive alkaloid from the males at mating, apparently by seminal infusion, and transmit this alkaloid together with alkaloid of their own to the eggs. Field and laboratory tests showed that the alkaloids protect eggs from predators. The alkaloidal contribution of the male, although smaller than that of the female, itself provides significant egg protection. A previously identified pheromone, derived by the male from the alkaloid and emitted during precopulatory behavior, may announce the male alkaloidal worth to the female.